Mini review on emerging methods of preparation of liposome and its application as Liposome drug delivery systems - Ateeq Rahman; Veikko Uahengo; Daniel Likius (Open Journal of Pharmacology and Pharmacotherapeutics - Peertechz Publications, 2018)
Liposomes, sphere-shaped vesicles consisting of one or more phospholipid bilayers, were fi rst described in the mid-60s. Nowadays, they are a very useful reproduction, reagent, and device in various scientifi c disciplines, including medicine, chemistry, biochemistry, colloid science, biology, physics, biophysics, mathematics and theoretical. After the initial discoveries liposomes have made their way to the market. Among numerous brilliant new drug delivery systems developed, liposomes characterize an advanced technology to deliver active molecules to the site of action, and at present, several formulations are in clinical use. Research on liposome technology has progressed from conventional vesicles to 'second-generation liposomes', in which long-circulating liposomes are obtained by modulating the lipid composition, size, and charge of the vesicle. Liposomes with modifi ed surfaces have also been developed using several molecules, such as glycolipids or sialic acid. This paper mini review summarizes exclusively Nano-lipids, its applications in medicine scalable techniques in treating dreadful diseases cancer, AIDS, paralysis etcand focuses on strengths, respectively, limitations in respect to industrial applicability and regulatory requirements concerning liposomal drug formulations based on FDA and EMEA documents.